HIGH CURIE TEMPERATURE xBiScO3-(1-x)PbTiO3 CERAMICS - Shahzad, K.; Khan, M. N.; Bashir, J. (The Nucleus, 2011)
Perovskite solid solution of xBiScO3- (1-x)PbTiO3 (BSPT) nano-sized powders were successfully synthesized via solgel process and investigated as possible candidates for high temperature piezoelectric applications engines for pressure, force and vibration sensors. The structure and morphology of the powders was investigated with x-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The Curie temperature (Tc) observed to be 478Â° C is higher than any previous reported value.